PROSEDUR PENERAPAN PAJAK PENGHASILAN PASAL 21 ATAS KARYAWAN TETAP MENGGUNAKAN METODE E-SPT PADA PT. ARTAPRIMA CIPTA CATURINDO KOTA DEPOK - Dhandy Yusuf (2021)
Income tax (PPh) article 21 is an income tax imposed on income in the form of salaries, wages, honoraria, allowances and other payments made by individual domestic taxpayers. Taxes have a very large role in generating domestic cash receipts in order to realize the continuity and increase of national development. However, currently there are still many taxpayers who are still confused and don't even understand how to calculate the amount of income tax from the salary they receive. From these problems, this research is made to build an application, namely "The Method of Calculating Income Tax Article 21 on Employee Payroll Systems". By using this application, the process of calculating Income Tax Article 21 on the employee's payroll system can be done easily and automatically without any errors such as manual calculations that allow errors to occur, as well as to minimize errors in data management so that the resulting information is faster and more accurate.. Keywords: Procedure, Income Tax Aplication ,Permanent Imployees, e-spt Method